Answer:
x=2
Step-by-step explanation:
-3*(x-2)-(2*x-3)-(5-(4*x-2))=0
((0 - 3 • (x - 2)) - (2x - 3)) - (7 - 4x) = 0
2 - x = 0
-x+2 = 0
Subtract 2 from both sides of the equation :
-x = -2
Multiply both sides of the equation by (-1) : x = 2
Answer: 2
Step-by-step explanation:
Slope=rise/run
In this case
Rise=2
Run=1
2/1=2
Answer:
1) f=−8/7 2) z=−3/7
Step-by-step explanation:
1)-f+8=-8f
−f+8=−8f
Step 1: Add 8f to both sides.
−f+8+8f=−8f+8f
7f+8=0
Step 2: Subtract 8 from both sides.
7f+8−8=0−8
7f=−8
Step 3: Divide both sides by 7.
7f/7=−8/7
f=-8/7
2) 6z-5=-z-8
6z−5=−z−8
Step 1: Add z to both sides.
6z−5+z=−z−8+z
7z−5=−8
Step 2: Add 5 to both sides.
7z−5+5=−8+5
7z=−3
Step 3: Divide both sides by 7.
7z/7=−3/7